Philippines : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2011)
This paper estimates potential growth in the Philippines using different methodologies, and discusses growth prospects for the medium term. Several approaches can be used to estimate potential growth. It also describes a forecasting and monetary policy analysis system (FPAS) model. Using the estimated parameters and distributions for the stochastic shocks, solutions are derived for the variability in inflation and the output gap under alternative monetary policy reaction functions. Further work could extend the FPAS model for the Philippines in a number of directions.